GAMBARAN FAKTOR RESIKO LEPTOSPIROSIS PADA DATARAN TINGGI MENGGUNAKAN PEDOMAN KERAWANAN LEPTOSPIROSIS DI DATARAN TINGGI DENGAN LOKASI PENELITIAN KABUPATEN SEMARANG - Raysha Afiff; Mateus Sakundarno Adi; Lintang Dian Saraswati; M. Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Leptospirosis is a disease caused by the bacteria Leptospira sp. which can be transmitted from animals through blood or urine. This disease, which was originally developed in the lowlands in recent years, has begun to reach the highlands. The aim of this study is to describe the risk factors for Leptospirosis in the highlands by using guidelines for determining Leptospirosis susceptibility in the highlands. This type of research is descriptive, with the survey method and observation using a cross-sectional design, which is a research method carried out only in a certain period. The population of this study was 300 houses spread over 5 sub-districts in the Semarang highlands. Risk factors that are used as indicators include; temperature, humidity, altitude, condition of the walls of the house, ownership of livestock, the presence of rats, waste disposal facilities, vegetation, and sources of clean water supply. From these indicators, we conclude there is still many risk factors of Leptospirosis even in highland. Which mean Leptospirosis has developed and need early system to prevent the occurrence.